2000
DOI: 10.1007/s004120050425
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of a long terminal repeat-like element on the Y chromosome of the platyfish, Xiphophorus maculatus

Abstract: The platyfish (Xiphophorus maculatus), in which sex chromosomes are evident from stable and predictable inheritance of sex, is one of the best-studied lower vertebrates with respect to sex determination. In order to identify the structural equivalent for this in the karyotype, which does not contain heteromorphic pairs of chromosomes, two sex-linked molecular probes were used for fluorescent in situ hybridization analysis. One probe, derived from the melanoma oncogene locus ONC-Xmrk, stained both the X and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…These systems might be in the stages of early differentiation (Nanda et al, 2000), or highly differentiated according to morphology and/or structure. Multiple sex chromosomes usually arise from centric/tandem fusions or translocations between ancestral sex chromosome and autosomes.…”
Section: Introductionmentioning
confidence: 99%
“…These systems might be in the stages of early differentiation (Nanda et al, 2000), or highly differentiated according to morphology and/or structure. Multiple sex chromosomes usually arise from centric/tandem fusions or translocations between ancestral sex chromosome and autosomes.…”
Section: Introductionmentioning
confidence: 99%
“…clear correlation between these sequences and sex chromosomes has been established by numerous studies (e.g., Nanda et al 1990Nanda et al , 2000Matsubara et al 2006;Kejnovsky et al 2009) including several Neotropical fish groups (e.g., Parise-Maltempi et al 2007;Cioffi et al 2011Cioffi et al , 2012Machado et al 2011), suggesting that the differentiation of sex chromosomes' mechanism is often associated with the accumulation of repetitive DNA. Accordingly, repetitive sequences represent a powerful tool to elucidate both the processes of morphological differentiation of sex chromosomes in fishes and to possibly understand some of the diversity of the differentiation systems observed in this group of vertebrates (Cioffi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of repetitive DNAs have been associated to sex chromosomes, somehow relating to the diversity of genomes and evolutionary pathways behind this differentiation in fishes, e.g., Xiphophorus maculatus (Günther, 1866) (Nanda et al 2000;Zhou et al 2006) and Hoplias malabaricus (Cioffi et al 2011). For example, various studies have reported the accumulation of retroelements in the sex chromosomes of several taxa (e.g., Steinemann & Steinemann 1992;Cermak et al 2008;Ferreira et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…has greatly contributed to the study of fish karyotypic evolution, not only because this method provides additional information about the structure of their chromosomes but also because it allows the comparison of genomes of different species (Nanda et al, 2000). In fact, the repetitive DNA fraction of the genome was effective in identifying significant genomic changes that occurred during the differentiation of these karyomorphs of H. malabaricus.…”
Section: Hoplias Malabaricusmentioning
confidence: 99%